The Effectiveness of Implementing Law Number 23 of 2004 Concerning the Elimination of Domestic Violence in The City of Palopo - Kusmawati Kusmawati; Hambali Hambali; Aan Aswari (Fakultas Hukum Dehasen, 2024)
This research was conducted with the aim of: (1) knowing and analyzing the effectiveness of implementing Law Number 23 of 2004 on eliminating domestic violence in Palopo City; (2) knowing and analyzing the factors that influence the effectiveness of implementing Law Number 23 of 2004 concerning the elimination of domestic violence in Palopo City. This research uses primary data through data obtained through field research with parties related to this research, totaling 20 respondents. The results of this research indicate that the implementation of the Law on the Elimination of Domestic Violence in Palopo City is still less effective, this is assessed from the data obtained by the author, namely that acts of domestic violence are increasing every year. The factors that influence the effectiveness of the Law on the Elimination of Domestic Violence in Palopo City are community factors with a percentage of 36% of the 50 respondents, followed by law enforcement factors at 20%, legal factors at 18%, cultural factors at 16%, and facility and environmental factors. supporting facilities 5%.